Role of emotional intelligence in PR specialist’s career - S. A. Musatova (Вестник университета, 2023)
The article studies the relevance of the problems of emotional intelligence (EI) in the framework of PR-specialist’s career. The article presents concepts of emotional intelligence from the point of understanding specifics of the phenomenon, considers the typology of EI models, and investigates the problem of measuring emotional intelligence and prospects for developing this type of intelligence in PR-specialists. Emotional intelligence is a person’s ability to recognize and understand their own emotions, explain them, and, using the same ability, understand emotional reactions of others. The role of EI in PR-specialist’s career from the point of competence approach to professional activity has been considered. Vacancies content analysis data with employers’ requirements to the PR-specialist position have been compiled, table of references to personal qualities that can be attributed to the EI sphere made, and theoretical analysis of emotional intelligence carried out.